CURCUMIN PREVENTS COCHLEAR OXIDATIVE DAMAGE AFTER NOISE EXPOSURE - Haryuna, Tengku Siti Hajar; Riawan, Wibi; Reza, Muhammad; Purnami, Nyilo; Adnan, Adlin (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To demonstrate curcumin as the safe and effective therapeutic agent in the prevention and treatment of oxidative damage in fibroblasts within the cochlear supporting tissues and lateral wall following noise exposure by neutralizing oxidative stress-inducing agents, such as malondialdehyde (MDA) and hydrogen peroxide (H2O2). Methods: Twenty-four Rattus norvegicus were randomly divided into 4 groups (n = 6). Group 1: The control group; group 2: noise (+); group 3: noise (+), 50 mg/day curcumin (+); group 4: noise (+), 100 mg/day curcumin (+). All groups (except group 1) were subjected to 100 dB SPL for 2 h per day for 14 d. Curcumin used in this study was derived from Curcuma longa L. (Turmeric) with curcumin [28.1Â±1.0]% w/w compared to Standard and administered orally for 14 d. All samples were Immuno histo-chemistrically examined for the expressions of MDA in cochlear fibroblasts and colorimetrically examined for H2O2 levels in cochlear tissues using the colorimetric reader. Results: The results obtained showed significant differences for the expressions of MDA (P<0.05) in all groups, and significant differences for H2O2 levels (P<0.05) in all groups, except in group 1 compared to 4 and group 3 compared to 4. Conclusion: Curcumin proved to be potentially effective in the prevention and treatment of oxidative damage in fibroblasts within the cochlear supporting tissues and lateral wall following noise exposure by decreasing the expressions of MDA and H2O2 levels. Â